Exploring the Effect of Cooperation in Reducing Implicit Racial Bias and Its Relationship With Dispositional Empathy and Political Attitudes - Patané, Ivan; Lelgouarch, Anne; Banakou, Domna; Verdelet, Gregoire; Desoche, Clement; Koun, Eric; Salemme, Romeo; Slater, Mel; Farnè, Alessandro (Frontiers in Psychology, 2020)
Previous research using immersive virtual reality (VR) has shown that after a short period of embodiment of White people in a Black virtual body their implicit racial bias against Black people diminishes. Here we tested the effects of some socio-cognitive variables that could contribute to enhancing or reducing the implicit racial bias. The first aim of the study was to assess the beneficial effects of cooperation within a VR scenario, the second aim was to provide preliminary testing of the hypothesis that empathy and political attitudes could contribute to implicit bias about race, while the third aim was to explore the relationship between political attitudes and empathy. We had (Caucasian) participants embodied in a Black virtual body and engaged either in a cooperative (Coop group) or in a non-cooperative (Neutral group) activity with a confederate experimenter embodying another Black avatar. Before and after VR, we measured participants’ implicit racial bias by means of Implicit Association Test (IAT) and their perceived closeness toward the confederate experimenter. Before VR we also assessed participants’ political attitudes and empathy traits. Results revealed that, as compared to the Neutral group, the Coop group showed lower IAT scores after the social interaction. Interestingly, in the Neutral but not the Coop group the perceived closeness toward the confederate experimenter was associated with the initial racial bias: the more the participants reduced their distance, the more they reduced their IAT score. Moreover, reported traits of empathy and political attitudes significantly explained the variance observed in the initial implicit bias, with perspective-taking, empathic concern, and personal distress being significant predictors of the IAT scores. Finally, there was a relationship between political attitudes and empathy: the more participants considered themselves as left-wing voters, the higher their perspective-taking and empathic concern scores. We discuss these findings within the neuroscientific and social cognition field and encourage scholars from different domains to further explore whether and under which conditions a given manipulation for reducing racial bias could be efficiently transposed in VR.